Investigation of Groundwater Quality for Drinking Usage in Kifri District (Iraq) by using NPI and WQI Indices: Investigation of groundwater quality for drinking usage in Kifri District - Abdulmutalib Raafat Sarhat; Muhammad Mohsin; Aram Hassan Mohammed (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2022)
The present study was mainly proposed to investigate the quality of groundwater for drinking in Kifri District. The main aim of this study was to identify some pollutants of groundwater using two types of indexes which are: Nemerow’s pollution index (NPI) and Water quality index (WQI). The groundwater samples were collected from 36 stations (deep wells) and analyzed for seven physico-chemical parameters including EC, TDS, pH, TH, TA, Ca+2 andSO4-2; as well as, the results were compared to WHO standards. The results presented undesirable values for almost all physico-chemical parameters, according to WHO standard limits for drinking. Based on WQI, the results show that 33 stations out of 36 were classified under the ‘Poor Quality’ category. Also, most of the NPI values of EC, TDS, Ca+2, TH, TA, and SO4-2 concentrations were (>1) and exceeded the WHO standard. Thus, all the stations reported high values of WQI and NPI and all the groundwater samples belonged to polluted water.